Grazing disturbance increased the mobility, pathogenicity and host microbial species of antibiotic resistance genes, and multidrug resistance genes posed the highest risk in the habitats of wild animals - Zou, Shuzhen; Lu, Tan; Huang, Cailiang; Wang, Jie; Li, Dayong (Frontiers in Environmental Science, 2023)
There are frequent exchanges of antibiotic-resistant bacteria and their antibiotic resistance genes (ARGs) between the external environment or livestock and wild animals. Grazing disturbance (GD) is a major factor that causes dramatic changes in China's nature reserves. Studying the risk of ARGs in China's nature reserves under GD has great significance for assessing the health of the habitats where wild animals live. In our study, the potential ecological risks of ARGs in soil microorganisms of wild animal habitats under GD were analyzed. Our results showed that the diversities of the ARGs in GD were higher than those in check control (CK) that not be disturbed by grazing, and 46 types of ARGs were only checked in GD. The ARGs were only carried by plasmids, and their relative abundances and the numbers of ARGs carried by plasmids were increased by GD, six types of transferred open reading frames (ORFs) carrying ARGs were detected only in GD. GD increased the relative abundances of drug-resistant pathogens, and the pathogen, Acinetobacter baumannii ACICU, that was only found in GD. Our results indicated that GD increased the risk of ARGs to the habitat of wild animals by reducing the total soil microbial species, increasing the numbers, species and mobility of ARGs in soil microorganisms and the species and abundance of drug-resistant pathogens in soil, as well as the ARG carrying capacity of microorganisms. Multidrug resistance genes (MRGs) posed the highest risk in the habitats of wild animals, and GD increased its risk because the largest proportion of ARGs carried by microorganisms were MRGs, which were also the most abundant ARGs carried by plasmids, and the highest proportion of ARGs carried by Proteobacteria (the dominant host bacterium of ARGs) were MRGs. Thus, GD may cause microorganisms in the habitats of wild animals become resistant to many antibiotics. MRGs in soil microorganisms could be used as an indicator for predicting the risk of GD in the habitats of wild animals.